(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To determine the causes of orthopedic implants failure, which is being used in our setup for fixation of different fractures. Materials and Methods: The study was conducted at Orthopedic and Spine surgery unit of Hayatabad Medical Complex (HMC) Peshawar from November 2007 to May 2014. A total of 62 patients were retrospectively identified an included in the study. The inclusion criteria was adult patients of both gender under 45 years of age, who presented to our unit with complaints of pain, deformity or inability to bear weight after fixation of fracture of either limb. Exclusion criteria were age above 45 years, pathological fractures, diabetes mellitus, recent significant trauma, radiologically osteoporotic bones of any cause and infected implants. Type of fracture and implant used whether proper or not and adherence to AO trauma surgery principles were also assessed. Results: A total of 62 patients admitted with broken (failed) implants. There were 55 male and 7 female with a mean age of 38 years (18 to 45 years). They presented with failed DCP, ILN, Dynamic Hip Screw, Dynamic compression screw, IM nail, Schanz screws, Austin moor prosthesis and AO cannulated screws Conclusion: The most important causes of implant breakage are combination of biological and metallurgical. Commonest metallurgical cause attributable to implant failure was corrosion. Biological causes include selection of implant, surgical techniques, post operative care and fracture geometry. Key Words: Broken implants, corrosion, implant failure